2018
DOI: 10.3390/met8121062
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Hydrometallurgical Recovery of Valuable Elements from Spent Nickel–Metal Hydride HEV Batteries

Abstract: In the present study, the recovery of valuable metals from a Panasonic Prismatic Module 6.5 Ah NiMH 7.2 V plastic casing hybrid electric vehicle (HEV) battery has been investigated, processing the anode and cathode electrodes separately. The study focuses on the recovery of the most valuable compounds, i.e., nickel, cobalt and rare earth elements (REE). Most of the REE (La, Ce, Nd, Pr and Y) were found in the anode active material (33% by mass), whereas only a small amount of Y was found in the cathode materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 40 publications
0
15
1
1
Order By: Relevance
“…The inorganic acids present a satisfactory performance during leaching and achieve higher efficiency of metal extraction than organic acids [29]. Techniques that are used to prepare the final products from the leaching filtrate include solvent extraction [10,[30][31][32][33], electrochemical techniques [34][35][36], selective precipitation [21,[37][38][39][40], and co-precipitation [41][42][43]. Among these, co-precipitation is the most efficient technique for the recovery of more than one metal (mixed metal) due to a higher level of homogeneity and spherical/sphere-like products [44].…”
Section: Introductionmentioning
confidence: 99%
“…The inorganic acids present a satisfactory performance during leaching and achieve higher efficiency of metal extraction than organic acids [29]. Techniques that are used to prepare the final products from the leaching filtrate include solvent extraction [10,[30][31][32][33], electrochemical techniques [34][35][36], selective precipitation [21,[37][38][39][40], and co-precipitation [41][42][43]. Among these, co-precipitation is the most efficient technique for the recovery of more than one metal (mixed metal) due to a higher level of homogeneity and spherical/sphere-like products [44].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrometallurgical processes are the main alternative for recycling NiMH batteries, in which battery powders are generally leached in a mineral acid, such as HCl (around 40 % of the recent literature) or H 2 SO 4 (about 60 %) . To a minor extent, a few researchers have studied the use of HNO 3 , carboxylic acids, or ascorbic acid as leaching agents, but these have not been considered in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrometallurgical processes are the main alternative for recycling NiMH batteries, in which battery powders are generally leachedi namineral acid, such as HCl [13,[16][17][18][19][20][21][22][23] (around 40 %o f the recentl iterature)o rH 2 SO 4 (about 60 %). [2, 3, 28-32, 10, 12, 14, 18, 24-27] In view of as ustainable recycling process, the leaching mechanisms of nickel and rare-earth elements (REEs) contained within industrial samples of spent nickel metal hydride battery powders were investigated in HCl and H 2 SO 4 ,u nder mild temperature( 25-60 8C) and pH (3-5.5).…”
Section: Introductionmentioning
confidence: 99%
“…Korkmaz [17]. Korkmaz et al also reported a HCl acid leaching and oxalic acid precipitation route for the recovery of REM from waste NiMH batteries [18]. Innocenzi and Vegliò reported REM recovery by H 2 SO 4 leaching followed by a (REM) 2 SO 4 precipitation route using NaOH [19].…”
Section: Introductionmentioning
confidence: 99%